A Multicenter Study of Intramedullary Rodding in Osteogenesis Imperfecta. Issue 3 (July 2020) - Rodriguez Celin, Mercedes; Kruger, Karen M.; Caudill, Angela; Nagamani, Sandesh C.S.; Harris, Gerald F.; Smith, Peter A.
Abstract : Background: Osteogenesis imperfecta (OI), a heritable connective tissue disorder with wide clinical variability, predisposes to recurrent fractures and bone deformity. Management requires a multidisciplinary approach in which intramedullary rodding plays an important role, especially for moderate and severe forms. We investigated the patterns of surgical procedures in OI in order to establish the benefits of rodding. The main hypothesis that guided this study was that rodded participants with moderate and severe OI would have lower fracture rates and better mobility. Methods: With data from the Linked Clinical Research Centers, we analyzed rodding status in 558 individuals. Mobility and fracture data in OI Types III and IV were compared between rodded and non-rodded groups. Univariate regression analyses were used to test the association of mobility outcomes with various covariates pertinent to rodding. Results: Of the individuals with OI, 42.1% had undergone rodding (10.7% of those with Type I, 66.4% with Type III, and 67.3% with Type IV). Rodding was performed more frequently and at a younger age in femora compared with tibiae. Expanding intramedullary rods were used more frequently in femora. In Type III, the rate of fractures per year was significantly lower (p ⩽ 0.05) for rodded bones. In Type III, the mean scores on the Gillette Functional Assessment Questionnaire (GFAQ) and Brief Assessment of Motor Function (BAMF) were higher in the rodded group. However, Type-IV non-rodded subjects had higher mean scores in nearly all mobility outcomes. OI type, the use of expanding rods in tibiae, and anthropometric measurements were associated with mobility outcomes scores. Conclusions: Current practice in 5 orthopaedic centers with extensive experience treating OI demonstrates that most individuals with moderate and severe types of OI undergo rodding procedures. Individuals with severe OI have improved mobility outcomes and lower fracture rates compared with their non-rodded peers, which suggests that early bilateral rodding benefits OI Type III. Our analysis showed a change in practice patterns in the final years of the study in the severe forms, with earlier and more simultaneous rodding procedures performed. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.